2009
DOI: 10.1002/cmdc.200800411
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Promiscuity: Dependence on Compound Properties and Target Specificity in a Set of Recent Roche Compounds

Abstract: The term "pharmacological promiscuity" describes a compound's pharmacological activity at multiple targets. Pharmacological promiscuity is undesired in typical drug discovery projects, which focus on the "one drug-one target" paradigm. Off-target activity can lead to adverse drug reactions, or can obscure pharmacodynamic effects in animal models. Therefore, advanced lead compounds, pharmacological tool compounds, and drug candidates are usually screened against panels of safety-relevant targets to detect unwan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
117
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(133 citation statements)
references
References 31 publications
14
117
1
1
Order By: Relevance
“…17 In accordance with the previous results represented by 15 and 17, compound 20 having an ether moiety showed better potency; by a slight modification of the headgroup (22), the PI4KIIIα selectivity was further strengthened. Toward this end, we have successfully discovered a novel PI4KIIIα inhibitor having superb PI4KIIIα potency.…”
supporting
confidence: 88%
“…17 In accordance with the previous results represented by 15 and 17, compound 20 having an ether moiety showed better potency; by a slight modification of the headgroup (22), the PI4KIIIα selectivity was further strengthened. Toward this end, we have successfully discovered a novel PI4KIIIα inhibitor having superb PI4KIIIα potency.…”
supporting
confidence: 88%
“…In some disease etiologies, targeting multiple proteins may improve the therapeutic efficacy, such as for antipsychotic drugs or kinase inhibitors with anticancer activity (1). However, off-target activity can lead to adverse drug reactions (ADR) such as the case with fenfluramine and torcetrapib, 2 agents halted in development because of fatal hypertension that was the consequence of secondary target inhibition (1)(2)(3). Highlighting the promiscuity of small molecule inhibitors, a recent in silico screening of 213 Roche compounds revealed an average of 6.3 target proteins per compound (1).…”
Section: Introductionmentioning
confidence: 99%
“…However, off-target activity can lead to adverse drug reactions (ADR) such as the case with fenfluramine and torcetrapib, 2 agents halted in development because of fatal hypertension that was the consequence of secondary target inhibition (1)(2)(3). Highlighting the promiscuity of small molecule inhibitors, a recent in silico screening of 213 Roche compounds revealed an average of 6.3 target proteins per compound (1). The standard approach for detecting off-target activity consists of screening compounds against panels of targets, often involving recombinant proteins in cell-free systems, and in silico prediction tools (1,4).…”
Section: Introductionmentioning
confidence: 99%
“…Other molecular properties such as ionization state, basicity, and presence of certain functional groups have also been found to influence promiscuity. [6][7][8][9][10] Hopkins et al 6 reported that compound promiscuity decreases with higher molecular weight (MW) based on HTS data. Diller and Hobbs 11 published a statistical analysis of a company's historical HTS data, in which they examined the relationship between physicochemical properties, substructures, and likelihood of displaying biological activity, irrespective of target class.…”
Section: Introductionmentioning
confidence: 99%